The problem of euro-orphanhood of a young children in a contemporary family. - Jolanta Karbowniczek (Jesuit University Ignatianum in Krakow, 2012)
Euro-orphanhood is a very serious problem in modern Polish families. It applies to young children as early as preschool and primary as well as adolescents. More and more young, unemployed parents go outside the country for profit, leaving the children alone or in the care of grandparents, aunts, neighbours, etc. This article explains the concept: euro-orphanhood and migration. Brings closer the importance of euro-orphanhood in the lives of individuals, it also identifies the negative impact of labour migration of parents on a child's development and  raising at home and at school.   Eurosieroctwo stanowi bardzo poważny problem we współczesnych rodzinach polskich. Dotyczy ono najmłodszych dzieci już w wieku przedszkolnym i wczesnoszkolnym, a także dorastającej młodzieży. Coraz więcej młodych, bezrobotnych rodziców wyjeżdża poza granicę kraju w celach zarobkowych, pozostawiając dzieci same bądź pod opieką dziadków, ciotek, sąsiadów itp. W artykule wyjaśniono pojęcia: eurosieroctwo i migracja. Przybliżono znaczenie eurosieroctwa w życiu jednostki oraz określono negatywny wpływ migracji zarobkowej rodziców na rozwój i wychowanie dziecka w domu i w szkole.